17P deleted multiple myeloma presenting with intracranial disease: durable remission after tailored management. Issue 3 (15th June 2015) - Lee, Joe; Smith, Dean; Rabin, Neil; Tobias, Jeffrey; Yong, Kwee
Abstract: In multiple myeloma (MM), del(17p) is associated with a poor outcome if present in greater than half the tumour cells. Similarly, intracranial involvement, often seen in the context of advanced disease, also heralds short survival. We present a rare case of MM presenting with intracranial disease and carrying del(17p) in 100% of tumour cells. This patient was successfully treated with combination chemotherapy employing central nervous system directed agents and bortezomib, followed by autologous stem cell transplant and consolidation with radiotherapy, bortezomib and thalidomide. We also present the outcomes of our single‐centre experience of MM patients presenting with del(17p) disease. Copyright © 2015 John Wiley & Sons, Ltd.